YIA6 Effects of GLP-1 eluting stem cell therapy on collagen remodelling, infarct size and apoptosis in a porcine model of myocardial infarction. Issue 17 (26th August 2010) - Wright, E J; Farrell, K A; Wallrapp, C; Geigle, P; Lewis, A L; Stratford, P W; Malik, N; Holt, C M
Abstract : Glucagon-like peptide-1 (GLP-1) is a gut incretin hormone with cardioprotective effects. Human stem cells secreting a GLP-1 fusion protein and encapsulated in an alginate matrix (GLP-1 CellBeads) have been developed as a novel therapeutic agent. This study investigated the effects of GLP-1 CellBeads on post-myocardial infarction (MI) healing in a porcine model. GLP-1 CellBeads were delivered to the left anterior descending coronary artery to create micro-infarcts, with cell-free beads as controls. Hearts were explanted at 1 and 4 weeks post-MI. Gross infarct size was measured as a percentage of left ventricular area. Tissue was analysed for inflammation (number of MAC 387 positive cells/mm 2 ), apoptosis (% TUNEL positive cells) and collagen (% picrosirius red staining). Compared with controls (n=4), the GLP-1-treated group (n=6) exhibited less infarct at one (6.21%±0.64 vs 9.78%±1.80% 2LV, p=NS) and 4 weeks post-MI (4.7%±2.1 vs 21.8%±4.8% LV, p=0.02). Within the infarct there was increased inflammation in GLP-1-treated groups at both time points (1 week: 97.22%±19.62 vs 36.67%±7.78, p=0.01; 4 weeks: 24.2%±4.57 vs 12.3%±3.16, p=0.03). At 1 week, apoptosis rates in the infarct area were similar in both groups (1.46 %±0.57 vs 1.47 %±0.17, p=NS), with less apoptosis in the GLP-1-treated group at 4 weeks (0.51%±0.18 vs 1.84%±0.62, p=NS). Collagen content at 1 week was lower (5.14%±1.19 vs 9.95%±1.42, p=0.05) and at 4 weeks higher in the treated group (20.89%±8.25 vs 6.87%±2.92, p=NS). GLP-1 CellBeads have an effect on post-MI infarct size, inflammation and ventricular remodelling. These findings require further validation before clinical translation.